Global research on sport tourism in commerce, management, tourism, and services : bibliometric analysis - Sri Rizki Handayani; Rizal Ahmad Fauzi; Amung Ma'mun; Vanessa Gaffar; Mustika Fitri; Farcham Mulloh; Wawan Junresti Daya; Harmaman Harmaman; Aldilla Yulia Wiellys Sutikno; Raisalam D. Angoy; Yovhandra Ockta; Rifqi Festiawan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction and Objective: This study analyzes trends in publications, citations, researcher activities, and co-occurrence visualizations on sport tourism using bibliometric analysis. The aim is to identify patterns in research development, explore emerging topics, and highlight research gaps, particularly the connection between sport tourism and sports events, as well as cultural preservation policies. Methodology: Data from the Scopus database, covering the period from 2000 to 2023, were analyzed using Dimensions and VOSviewer software. The analysis followed the PRISMA flowchart (identification, screening, and feasibility) and focused on articles related to sport tourism in the fields of commerce, management, tourism, and services. Results: The highest number of publications occurred in 2021, while the fewest were published in 2000. Co-occurrence network visualization revealed a strong link between sport tourism and sports events, but little connection to cultural preservation policies, indicating a research gap. Overlay visualization shows a trend towards the intersection of the sports industry and health tourism. Density visualization highlights high-density topics like sport tourism and event tourism, while topics such as sport heritage and nostalgia in sport tourism have low density. Conclusion: Future research should explore low-density topics, such as sport heritage and nostalgia in sport tourism, which remain underexplored and present potential areas for further investigation.